A simulation study of the cost of cerebral vasospasm treatments with clazosentan: A mathematical model using time-driven activity-based costing - Jieyu Zhao; Kota Kurisu; Kazuki Ohashi; Toshiya Osanai; Katsuhiko Ogasawara; Miki Fujimura (PLoS ONE, 2026)
In this work, we aimed to assess the impact of clazosentan on clinical labour time costs within Japan’s value-based healthcare system using time-driven activity-based costing. Time-driven activity-based costing was employed to analyse the labour time costs associated with preventing cerebral vasospasm following aneurysmal subarachnoid haemorrhage. Time-driven activity-based costing simplifies cost analysis by utilising time as the primary cost driver. We compared two treatment approaches: conventional therapy with fasudil hydrochloride and postoperative therapy with clazosentan. Scenario and sensitivity analyses were performed to assess the impact of physicians’ costs on the results. The use of clazosentan for the prevention of cerebral vasospasm significantly reduced human resource costs, particularly in cases where symptomatic vasospasm did not occur, yielding savings of approximately 51,343 yen. The greatest cost reductions were observed among nursing staff, with a 30% decrease in the absence of symptomatic vasospasm and a 15% reduction when symptomatic vasospasm was present. The cost reductions for physicians were comparatively smaller, particularly in cases where symptomatic vasospasm occurred. Sensitivity analyses indicated that clazosentan reduced overall costs by approximately 35,000–50,000 yen; however, costs increased in the presence of symptomatic vasospasm. Clazosentan for subarachnoid haemorrhage treatment significantly reduces human resource costs, especially in nursing staff. These findings support the potential of clazosentan for broader clinical use, given its cost-savings and clinical benefits in reducing cerebral vasospasm following aneurysmal subarachnoid haemorrhage.